Privatizing Airports-Options and Case Studies - Juan, Ellis J. (World Bank, Washington, DC, 2012)
Traditionally, the air transport sector--airlines, airports, and air navigation services--has been in state hands. The private sector became involved in the sector only recently, beginning with the airlines. Privatization of airport infrastructure and private sector participation in air navigation are also at an early stage. The air transport sector will require large capital investments over the next fifteen years to modernize aircraft fleets, improve airport infrastructure, introduce more sophisticated air navigation systems, and meet the demand of new markets. There is no doubt that governments will be unable to fund all necessary investments, and that the private sector will therefore play an increasing role in meeting the sector's needs. Table 1 in this Note presents three options of private sector participation in airports. Table 2 presents two options most suitable for transferring airport activities to the private sector. The Note also outlines cases of airport privatization in Colombia, Jamaica, Canada, and Northern Ireland.